PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN, DAN TARIF PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of tax planning, deferred tax expense and tax rates on earnings management in companies listed on the Indonesia Stock Exchange. The population in this study is a Manufacturing Company sub-sector of the Consumer Goods Industry listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This type of research is quantitative research using purposive sampling method, with a total sample of 14 companies. The analysis used in this research is descriptive statistical test, normality test, classical assumption test, multiple linear regression test and hypothesis testing. The results of this study indicate that based on the partial test (t test), Tax Planning has a significant effect on Earnings Management, Deferred Tax Expense has a significant effect on Earnings Management, while Tax Rates have no significant effect on Earnings Management. Simultaneously (F test), Tax Planning, Deferred Tax Expense, and Tax Rates have a significant effect on Earnings Management.Keywords : Tax Planning, Deferred Tax Expense, Tax Rates, and Earnings Management